FACE RECOGNITION SYSTEM USING CNN IN DEEP LEARNING (International Journal of Food and Nutritional Sciences, 2024)
Abstract:The Face Recognition System is a pivotal component of biometric security systems and has gained significant attention in recent years due to its wide range of applications in security, surveillance, and personal identification. This abstract proposes a System that aims to accurately identify individuals based on facial features extracted from images using the concepts of Deep Learning. The System employs deep learning algorithms such as Convolutional Neural Networks (CNN) for Feature extraction and classification. It is trained on a large dataset off acialimagestoenhanceaccuracy and robustness. It leverages the capabilities of OpenCV for face recognition tasks. Furthermore, it demonstrates promising results in facial recognition tasks, paving the way for enhanced security and personalized user experiences.